ANALISIS STRATEGI PROMOSI SYARIAH DALAM PENINGKATAN VOLUME PENJUALAN PETIS ARBA’ UD. KURNIA INDUSTRI MUNCAR BANYUWANGI - Ach. Zubairi; Nuril Firdausiyah; Daryoto Mulyadi Candra (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
Kurnia Industri has carried out a good promotional strategy in marketing the products it produces, so that consumers do not buy only from around UD. Industrial Gifts. The purpose of the promotion is to introduce the product produced to consumers and be influenced to buy it. The beginning of UD. Kurnia Industri introduces its products by word of mouth (Mouth of Mouth) which is carried out with surrounding consumers. UD. Kurnia Industri also pays attention to consumer confidence in arba' petis by maintaining the product quality of arba' petis itself. Management of sharia promotion carried out at UD. Kurnia Industri Muncar Banyuwangi is by doing personal selling, publicity, and also direct marketing. Creating trust, carrying out activities that can attract the attention of consumers and being honest in every transaction carried out are activities of every promotional strategy carried out by UD. Industrial Gifts.